PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) DALAM MENENTUKAN POSISI DUDUK PESERTA DIDIK - Moh Er Kamim; Rendy Bagus Pratama; Wartono Wartono; Kusrini Kusrini (STMIK Sinar Nusantara, 2018)
Learning process there are several factors that influence success rate of learners in receiving lessons. one of the supporting factors is a conducive classroom environment, a conducive class can be created with the ideal seating position arrangement. In the determination of sitting position at Girirejo Elementary School Nganjuk State conducted randomly so as to cause uneven seating position and resulted in the learning activities do not run optimally, there are students who should be in front of sitting behind and vice versa. To overcome these problems then it takes an election to determine the sitting position of learners in order to help guardians determine the sitting position in the class so as to create an ideal sitting position. In determining the sitting position used a method of Simple Additive Weighting (SAW) with the criteria of value, height, and the use of glasses, the method combined alternative search with seating object where seats are sought alternative value difference between the highest value and the lowest score of students, will be divided by the number of students, will be generated the highest value and the lowest value on each seat, so that will appear alternative to the seat to be occupied by students with the weight of the value entered in the value range on the seat. The final result in this research is not maximal in accordance with the planned because there are still vacant seats are not filled by the students, so it needs to be improved in the future to be able to find alternative every seat to be filled by all students so it can help teachers in mapping the ideal student sitting position in the classroom.